MEMBUMIKAN MULTIKULTURALISME SEBAGAI UPAYA PENCEGAHAN SIKAP RADIKALISME BERAGAMA - Ramdanil Mubarok; Maskuri Bakri (Fakultas Agama Islam Universitas Wiralodra Indramayu, 2021)
Accepting other people and other groups regardless of gender, ethnicity, culture, gender and even religion is a concept proposed in multiculturalism. This article will analyze and provide an interpretation of the characteristics of radicalism, efforts to prevent it, and grounding multiculturalism so that it can be an additional insight and experience in the survival of the nation and state. The approach used in this article is a qualitative approach. The type is the type of library research. The result is that radicalism is not only in the form of violence, anarchism, and terrorism but can also be a religious ideology. Efforts to prevent radicalism can be done by building different narratives about radicalism, paying attention to the characteristics of a culture, as well as real social action by planning, implementing, monitoring, and evaluating. Grounding multiculturalism cannot be separated from the life of religion, nation, state and cultural inheritance so that it needs to be studied, applied, and socialized.